CMOS low-power, fully-programmable Gaussian/Trapezoidal fuzzy membership function generator - Azizian, Sarkis (Informacije MIDEM, 2025)
Design of a novel flexible structure for fuzzy Membership Function Generator (MFG) has been discussed in this article. The main advantage of the proposed circuits is the capability for the production of all Trapezoidal, Gaussian, S and Z shapes, simultaneously. This objective has been achieved at the first step by means of two interconnected differential pairs which generate Gaussian, S and Z shapes. Thereafter, with the help of an improved Min/Max circuit, the Trapezoidal shape with sharp edges has been constructed. The circuits are designed in a way to produce all shapes with the feature of full programmability for slope, core, and height. These features, along with small active area and low power consumption, qualify this work to be repeatedly used in Fuzzy Logic Controllers (FLCs). Post-layout simulation results for TSMC 0.18µm CMOS technology confirm the correct behavior of the designed circuits. Based on the results, the power consumption of the whole structure is 54µW from a 1.8V power supply.
Keywords: fuzzifier; fuzzy funkcija; fuzzy logic controller; fuzzy membership function; krmilnik fuzzy logike; min/max circuits; min/max tokokrogi